Bound : over 20 artful handmade books - Ekrem, Erica; Havens, Sue (Asheville : Lark,an imprint of Sterling Publishing, 2015)
"Bound offers approximately 25-30 bookbinding projects showcasing beautiful exposed bindings. Classified in chapters entitled Vintage, Nature, and Leather, projects include a mason jar book, a seashell book, and a classic-looking leather-bound photo album, to name a few. Beginners will find plenty of entry-level projects to enjoy, while more experienced book artists will learn new ways to do old binding techniques. The Basics section and each project are illustrated with gorgeous, bright beauty shots and whimsical-but-clear illustrations. Ms. Ekrem uses her way with words and her talented hand at book arts to take readers on a little stroll into their own imagination (or their memory) with each creation"--
Includes index.
Keywords: Bookbinding -- Handbooks, manuals, etc; Book design -- Handbooks, manuals, etc